Morphometry of Demodex species in dogs - Sirigireddy Sivajothi; Sudhakara Reddy, Bhavanam (Indian Journal of Veterinary Medicine, 2024)
The present study was carried out to record the mean length and width of gnathosoma, podosoma and opisthosoma of two different Demodex mites in dogs. The mean lengths gnathosoma, mean width of gnathosoma, podosoma and opisthosoma did not differ significantly (P>0.05); mean length of podosoma, opisthosoma and the total body differed significantly (P